Prižiznennyj dogovor na okazanie ritual'nyh uslug v sisteme obâzatel'stv po ritual'nomu obsluživaniû - Zajcev, Oleg Aleksandrovič; Gračev, Roman Ûr'evič (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
In this speech, the author offers a classification of contracts of the ritual service, which get legal qualification, and determines their place in the system of contractual obligations. Special attention is paid to the social value, the legal nature of the lifetime of the contract for the provision of funeral services and analysis of imperfect legislation in this field. There are revelations of advantages and disadvantages of the proposed novel in the draft law «About the funeral business in the Russian Federation», designed to ensure fulfilment of the lifetime contract obligations for the provision of funeral services connected with insurance of civil responsibility of a specialized service for the funeral business. In order to increase guarantees the proper execution of this contract, it is grounded the necessity to legalize the construction of a tripartite agreement between the customer, executor and trustee who have agreed to take the responsibility to fulfill the will of the customer in the event of the death of the latter. It is offered to assign the status of the consumer of services to the executor of the will of the customer. Advantages of this legal construction in relation to offered by the bill also come to light
Keywords: lifetime contract; funeral services; funeral business; contract; death